2000
DOI: 10.1046/j.1365-313x.2000.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Brassica juncea 3‐hydroxy‐3‐methylglutaryl CoA synthase is developmentally regulated and stress‐responsive

Abstract: Summary 3-Hydroxy-3-methylglutaryl-coenzyme A synthase (HMGS) is an enzyme in mevalonate biosynthesis. In plants, investigations have focused on HMG CoA reductase (HMGR) and less is known of the preceding enzyme, HMGS. To understand the regulation of HMGS, we have isolated a Brassica juncea cDNA encoding HMGS, BjHMGS1, for use as a hybridization probe in Northern blot analyses. BjHMGS is expressed in all plant organs and shows developmental regulation in¯ower, seed and seedling, with highest expression in earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 76 publications
2
25
0
2
Order By: Relevance
“…, 2000). BjHMGS was down‐regulated by ABA, osmotic stress and dehydration and up‐regulated by salicylic acid (SA), methyl jasmonate (MeJA) and wounding (Alex et al. , 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2000). BjHMGS was down‐regulated by ABA, osmotic stress and dehydration and up‐regulated by salicylic acid (SA), methyl jasmonate (MeJA) and wounding (Alex et al. , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to investigate the effects of overexpression of wild‐type (wt) and mutant (H188N, S359A and H188N/S359A) BjHMGS1 in Arabidopsis thaliana Col‐0. HMGS overexpression in Arabidopsis HMGS‐OEs not only elevated the expression of HMGR , given that both are co‐ordinately regulated in B. juncea (Alex et al. , 2000), but SMT2, DWF1 , CYP710A1 and BR6OX2 , further down in the MVA pathway related to sterol biosynthesis, were also induced.…”
Section: Introductionmentioning
confidence: 99%
“…HMGS has been shown to play a crucial role in floral development [4], [34], [35], [37]. In Arabidopsis , higher AtHMGS expression had been observed in flowers than seedlings or leaves from RT-PCR analysis [4].…”
Section: Discussionmentioning
confidence: 99%
“…Using mutants in HMGS , AtHMGS was demonstrated essential for pollen fertility and proper development of tapetum-specific organelles in Arabidopsis [35]. In B. juncea , northern blot analysis had previously revealed that BjHMGS1 mRNA was highly expressed in flowers and seedling hypocotyls [34] and in situ hybridization analysis had shown that HMGS mRNA was predominantly localized in the stigmata and ovules of flower buds and in the piths of seedling hypocotyls [37]. BjHMGS1 and BjHMGS2 , but not BjHMGS3 and BjHMGS4 expression was detected in the floral buds as examined by RT-PCR analysis [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation